Gaziantep'te dînî mûsikî - Türkoğlu, Zeyneb (My University, 2020)
Gaziantep tarihi boyunca, farklı medeniyetlerin yaşadığı bir coğrafya içinde yer almasından dolayı geniş bir kültüre sahiptir. Pek çok dîvân şairine, bestekara, manevi büyüklere ev sahipliği yapan bu şehir, dînî mûsikî kültürü açısından da oldukça zengindir. Özellikle uzun yıllardır Gaziantep’teki tasavvufî hayat, geçmişten bugüne sahip olduğu mûsikî kültürünü koruyarak devam ettirmekte ve Gaziantep’te tekke mûsikîsi adına önemli bir kaynak görevi üstlenmektedirler. Bununla birlikte câmilerde uygulanan mûsikî de Gaziantep’e has üslûp ve uygulamalar taşımaktadır. Bu çalışmanın amacı, gerek tekke, gerekse cami uygulamaları olmak üzere Gaziantep’in dînî mûsikî kültürünü kaleme alıp, bir kaynak haline getirmektir. Bu amaçla öncelikle Gaziantep’in tarihi ve kültürü hakkında bilgiler vererek, akabinde buradaki mûsikî kültüründen bahsedip, ana konumuz olan dînî mûsikî araştırmaları paylaşılmıştır. Son olarak da tarihi ve güncel, Gaziantep ürünü olan ilâhilere ve bu ilâhilerin notalarına yer verilmiştir.

Gaziantep has a rich culture as it is located in a region inhabited by different civilizations throughout history. Home to many divan poets, composers and spiritual elders, this city also has a vast culure of religious music. Tekkes (i.e. Islamic monastries), which have been present in Gaziantep for many years, protect and resume their musical culture from the past to the present, and here, the Tekkes are an important source of tekke music. Moreover, the music performed in mosques also have styles and practices unique to Gaziantep.The aim of this study is to document Gaziantep's religious music culture, the practices in both tekkes and mosques, and to contribute to the literature by producing a resource for the religious music in the city. For this purpose, information regarding the history and culture of Gaziantep is firstly presented, the music culture in the region is then elaborated, followed by the research and studies on the main topic of this thesis, religious music. Finally, the hymns that are current or that go back in history, which were composed in Gaziantep, are covered along with their musical notes.
Keywords: Art; Cami; Câmi; Dînî Mûsikî; Gaziantep; History; Islam; İslam; Music; Müzik; Sanat; Tarih; Tekke; Tekke Gaziantep